1990
DOI: 10.1055/s-2007-1014534
|View full text |Cite
|
Sign up to set email alerts
|

Group Report 3: Early Clinical Testing of Cognition Enhancers: Prediction of Efficacy

Abstract: The major problem in predicting clinical efficacy from animal experimental results and phase I data is the lack of resemblance between the models used and the clinical condition. This problem is complicated by the diversity of the potential mechanisms of action of new compounds. A further question is whether Phase I studies should be used as predictors of clinical efficacy at all. Should they be used simply for determining pharmacologically active dose ranges and tolerance? If used as predictors should drug de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Several human models have been the subject of debate, particularly the scopolamine (hyoscine), benzodiazepine and hypoxia models of cognitive dysfunction. [37][38][39] The major problem in predicting clinical efficacy from human experimental results and phase I data is the lack of resemblance between the models used and the clinical condition. This problem is complicated by the diversity of the potential mechanisms of action of new compounds.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Several human models have been the subject of debate, particularly the scopolamine (hyoscine), benzodiazepine and hypoxia models of cognitive dysfunction. [37][38][39] The major problem in predicting clinical efficacy from human experimental results and phase I data is the lack of resemblance between the models used and the clinical condition. This problem is complicated by the diversity of the potential mechanisms of action of new compounds.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…The central nervous system (CNS) effects consist of drowsiness, reduced attention and memory impairment, and a range of other CNS effects including changes in several EEG frequency bands [4][5][6]. At present, scopolamine is the most extensively studied and documented model for cognitive deficits [7][8][9][10]. The scopolamine model is frequently used in preclinical studies of cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 ] The scopolamine-induced memory deficit model has been widely used for identifying the potential of drug candidates to reverse the effects of cholinergic blockade. [ 40 ] Scopolamine causes memory impairment through inhibition of cholinergic system. [ 41 ] It was shown that muscarinic acetylcholine receptors, causing the consolidation of spatial memory.…”
Section: Discussionmentioning
confidence: 99%